1995
DOI: 10.1084/jem.181.3.1091
|View full text |Cite
|
Sign up to set email alerts
|

FK506 inhibits antigen receptor-mediated induction of c-rel in B and T lymphoid cells.

Abstract: SunllTlaryStimulation of B and T cells via the antigen receptor, by phorbol ester or by phorbol ester and ionomycin, leads to nuclear translocation of the inducible transcription factor NF-KB, comprising the p50 and p65 re/-related polypeptides. In this report we show that c-tel is a component of the antigen receptor-induced xB binding proteins in both B and T cells. Whereas NF-~cB can be induced by phorbol ester alone, optimal induction of c-tel requires stimulation by both phorbol ester and ionomycin, the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 39 publications
6
65
0
Order By: Relevance
“…That is, FK506 can specifically block c-Rel nuclear translocation (but not p50/RelA) after treatment of cells with phorbol esters and ionomycin Venkataraman et al, 1995). Therefore, the antiproliferative effects of FK506 in T cells results from inhibition of NF-kB, which consequently blocks transcription of the IL-2 and IL-2 receptor genes by interfering with the induction of c-Reldependent transcription of their promoters (Serfling et al, 1995;Venkataraman et al, 1995). Interestingly, the effectiveness of topical administration of FK506 ointment in keratinocytes correlates with its anti-NF-kB activity (Lan et al, 2005), suggesting that inhibition of NF-kB may be responsible for FK506's effectiveness in psoriasis.…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, FK506 can specifically block c-Rel nuclear translocation (but not p50/RelA) after treatment of cells with phorbol esters and ionomycin Venkataraman et al, 1995). Therefore, the antiproliferative effects of FK506 in T cells results from inhibition of NF-kB, which consequently blocks transcription of the IL-2 and IL-2 receptor genes by interfering with the induction of c-Reldependent transcription of their promoters (Serfling et al, 1995;Venkataraman et al, 1995). Interestingly, the effectiveness of topical administration of FK506 ointment in keratinocytes correlates with its anti-NF-kB activity (Lan et al, 2005), suggesting that inhibition of NF-kB may be responsible for FK506's effectiveness in psoriasis.…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
“…However, unlike CsA, the inhibitory effect of tacrolimus on NF-kB appears, in some cases, to be specific for c-Rel, among the NF-kB family members. That is, FK506 can specifically block c-Rel nuclear translocation (but not p50/RelA) after treatment of cells with phorbol esters and ionomycin Venkataraman et al, 1995). Therefore, the antiproliferative effects of FK506 in T cells results from inhibition of NF-kB, which consequently blocks transcription of the IL-2 and IL-2 receptor genes by interfering with the induction of c-Reldependent transcription of their promoters (Serfling et al, 1995;Venkataraman et al, 1995).…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
“…These molecules were originally used as inhibitors of serine proteases, but were also found to act as proteasome Palombella et al, 1994;Grisham et al, 1999;Jobin et al, 1998a ALLnL (N-acetyl-leucinyl-leucynil-norleucynal Okamoto et al, 1994;Venkataraman et al, 1995Deoxyspergualin Tepper et al, 1995 Protease inhibitors inhibitors and to be more potent than are their aldehyde analogs (Grisham et al, 1999;Iqbal et al, 1995). An indirect method of blocking proteasomemediated degradation of IkB is by inhibiting the ubiquitin ligase that acts on IkB.…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…FK506 also has been reported to block NF-kB DNA binding in Jurkat T cells stimulated with phorbol ester (Okamoto et al, 1994). Therefore, the antiproliferative e ects of FK506 in T cells results from inhibition of Rel/NF-kB, which consequently blocks transcription of the IL-2 and IL-2 receptor genes by interfering with the induction of kB site-dependent transcription of their promoters (Ser¯ing et al, 1995;Venkataraman et al, 1995).…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
“…It was clear that Rel is a positive or negative regulator of transcription in macrophages and that Rel has distinct roles in different macrophage populations. Venkataraman et al showed that c-Rel is a component of the Ag receptor-induced, B binding proteins in both B and T cells (27). Moreover, there is evidence that c-Rel contributes to the survival of nerve growth factor-dependent sympathetic neurons (28), the human 12-lipoxygenase gene (29), and c-myc gene transcription (30).…”
Section: Figurementioning
confidence: 99%